2019
DOI: 10.2478/bjdm-2019-0011
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of Skeletal Class III

Abstract: Summary Skeletal Class III is a relatively rare malocclusion of the craniofacial complex and the accurate differential diagnosis of its aetiology is necessary so that it may be correctly treated. Differential diagnosis of Class III aetiopathogenesis should distinguish between: a) true skeletal Class III as opposed to pseudo Class III; b) three forms of Skeletal Class III, in which there is either maxillary deficiency only or mandibular excess only or combination of both; and c) skeletal Class III that may be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…It has been reported that in US population class III malocclusion mostly occurs as a maxillary hypoplasia and protrusion. In contrast, in Asians, this deformation is predominantly diagnosed with a normal upper jaw and the overgrowth of the mandible [83,84]. To avoid the misdiagnosis of improper upper jaw or mandible development, a lateral cephalometric radiograph with cephalometric analysis should be performed [84]; this is a standardized orthodontic method and a part of the diagnostic process of malocclusion and treatment planning.…”
Section: Mandibular Prognathism (Mp)-clinical Features and Manifestationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that in US population class III malocclusion mostly occurs as a maxillary hypoplasia and protrusion. In contrast, in Asians, this deformation is predominantly diagnosed with a normal upper jaw and the overgrowth of the mandible [83,84]. To avoid the misdiagnosis of improper upper jaw or mandible development, a lateral cephalometric radiograph with cephalometric analysis should be performed [84]; this is a standardized orthodontic method and a part of the diagnostic process of malocclusion and treatment planning.…”
Section: Mandibular Prognathism (Mp)-clinical Features and Manifestationmentioning
confidence: 99%
“…In contrast, in Asians, this deformation is predominantly diagnosed with a normal upper jaw and the overgrowth of the mandible [83,84]. To avoid the misdiagnosis of improper upper jaw or mandible development, a lateral cephalometric radiograph with cephalometric analysis should be performed [84]; this is a standardized orthodontic method and a part of the diagnostic process of malocclusion and treatment planning. Angular and linear measurements carried out on a radiograph allow for the assessment of the positions of various anatomical structures [85].…”
Section: Mandibular Prognathism (Mp)-clinical Features and Manifestationmentioning
confidence: 99%